Parent and Therapist Perceptions of the Feasibility, Acceptability, and Benefits of a Weekly Therapist-Led Massage Program for Extremely Preterm Infants in Neonatal Intensive Care - Dana B. McCarty; Stacey C. Dusing; Alana Gilbert; Kristen D. LeBlond; Meredith Soucie; T. Michael O'Shea (MDPI AG, 2023)
Mothers of extremely preterm infants experience high rates of mental health disorders that impair maternal-infant interaction and lead to worse infant developmental outcomes. Therapist Education and Massage for Parent-Infant Outcomes (TEMPO) is a therapist-led program that standardizes the nature and frequency of parent education through weekly scheduled therapy sessions. Using a family-centered approach, the therapist facilitates positive maternal-infant interactions and massage interventions from birth throughout hospitalization with the goal of improving maternal mental health. This qualitative study presents the results of 19 parent interviews and of a focus group of four TEMPO interventionists to elicit feedback about the program. Overall, parents and therapists viewed the program positively. Parents and therapists valued the focus on parent education and engagement to increase parent competence and bonding opportunities. Both groups acknowledged that infant massage had both infant-centered and parent-centered benefits. One area where parent and therapist views did not align was regarding feasibility of TEMPO. Parents noted multiple logistical challenges to regular NICU visitation, but ultimately agreed that attending weekly therapy sessions was feasible. Therapists noted increased time and effort required of TEMPO and felt that institutional and system-level changes would be necessary to implement weekly parent education as standard of care.